2015
DOI: 10.1038/jcbfm.2015.133
|View full text |Cite
|
Sign up to set email alerts
|

Blocking of Fatty Acid Amide Hydrolase Activity with PF-04457845 in Human Brain: A Positron Emission Tomography Study with the Novel Radioligand [11C]CURB

Abstract: Positron emission tomography with [11 C]CURB was recently developed to quantify fatty acid amide hydrolase (FAAH), the enzyme responsible for hydrolyzing the endocannabinoid anandamide. This study investigated the test-retest reliability of [ 11 C]CURB as well as its in vivo specificity and the validity of the kinetic model by using the highly specific FAAH inhibitor, PF-04457845. Five healthy volunteers completed test-retest [11 C]CURB scans 1 to 2 months apart and six subjects completed baseline and blocking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…Currently a clinical trial with the Pfizer FAAH inhibitor PF-04457845 (7173) is on-going for cannabis withdrawal (NCT01618656 at ClinicalTrials.gov). Our recent human blocking study with the Pfizer compound and [ 11 C]CURB PET provided crucial information on the dosing regimen that produces sufficient FAAH inhibition in the human brain (44). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently a clinical trial with the Pfizer FAAH inhibitor PF-04457845 (7173) is on-going for cannabis withdrawal (NCT01618656 at ClinicalTrials.gov). Our recent human blocking study with the Pfizer compound and [ 11 C]CURB PET provided crucial information on the dosing regimen that produces sufficient FAAH inhibition in the human brain (44). …”
Section: Discussionmentioning
confidence: 99%
“…The recently developed PET tracer [ 11 C]CURB ([ 11 C-carbonyl]-6-hydroxy-[1,10-biphenyl]-3-yl cyclohexylcarbamate (URB694)) (43) is an effective PET radioligand, which binds selectively and irreversibly to FAAH (44). We recently reported that FAAH binding can be estimated reliably and reproducibly (44) using a two-tissue compartment model with irreversible trapping (2-TCMi) that fitted regional time-activity curves, with the composite parameter λ k 3 (λ= K 1 /k 2 ) as the preferred index of FAAH binding (45). …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, two potent and irreversible fatty acid amide hydrolase (FAAH) inhibitors, [ 11 C]PF-04457845 [41] and [ 11 C]CURB [42], have also been prepared. The latter, [ 11 C]CURB, have recently been translated to a clinical setting for reginal quantification of FAAH activity in human brain [43]. Furthermore, the reversible monoamine oxidase B (MAO-B) radioligand, [ 11 C]SL25.1188, previously prepared using the technical demanding [ 11 C]phosgene approach, was radiolabeled in high yield via 11 CO 2 -fixation [44, 45].…”
Section: Co2-fixation Reactionmentioning
confidence: 99%
“…[ 11 C]CURB is an irreversible FAAH inhibitor that shows high brain uptake in rodents, with highest uptake levels in the cortex and cerebellum [24]. As with radiotracers targeting CB 1 , imaging with [ 11 C]CURB has been demonstrated to have good test-retest reliability [25]. There are several lines of evidence suggesting that [ 11 C]CURB provides an index of FAAH activity.…”
Section: Radiotracers Targeting the Endocannabinoid Systemmentioning
confidence: 99%